Zmožnejši bralci in pisci besedil v prvem razredu osnovne šole - Grom, Katarina (Revija za elementarno izobraževanje, 2016)
Advanced Readers and Writers of Texts in the First Class of Primary School. The paper focuses on determining reading and writing skills of children at the beginning and at the end of school year and on the introduction of a model test for the Cankar Award Contest. The objective of the present work is to develop a model for the Cankar Award Contest for children in the first year of primary school and to establish whether children in the first class are capable of participating in such a contest. Research on a sample of 55 children has yielded key conclusions about the capabilities of children in initial literacy and confirmed that pupils with advanced competences in the area of reading and writing are able to participate in the Cankar Award Contest, in which previously they could, as a rule, participate from the second class on.